Pengembangan Sistem Point of Sales Menerapkan Pendekatan PIECES - Telaumbanua, Kristian; Florida S. Damanik; Mirza Alhami; Erlanie Suparnap (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
The conventional method of recording and reporting sales transactions at PT. Teknologi Air Perkasa makes it difficult to find and access the data needed, and often loses data because it is only stored on a local computer. To solve the problems that have been described, a web and mobile based Point of Sales (POS) application is proposed. The POS application was developed with Waterfall software development method which then tested with black box testing method. After the application tested, it can be concluded that the POS application that had been developed is in accordance with the company’s needs, stores sales and product stock data online so that it can be easily accessed anytime and anywhere, produces sales reports and product stock reports which can simplify the operational of PT. Teknologi Air Perkasa and able to increase the competitiveness and customers’ attraction of PT. Teknologi Air Perkasa with the application of point system on every transaction and giving benefits in the form of discounts. The results of testing with the black box testing method that has been carried out on the POS application that has been developed, obtained data testing the functionality of application features that are appropriate as many as 233 and data testing the functionality of application features that are not suitable are 4 of the total tests carried out as many as 237, which means that the percentage for features in POS applications that have been developed whose functionality is appropriate is 98.3122% and the percentage for features in POS applications that have been developed whose functionality is not appropriate is 1.6878%, it can be concluded that features in web-based and mobile POS applications that have been developed in PT. Air Perkasa technology is already functioning according to the company's needs